Oil-Based Delivery Control Release System Targeted to the Later Part of the Gastrointestinal Tract-A Mechanistic Study - Lingping Zhang; Marie Wahlgren; Björn Bergenståhl (MDPI AG, 2022)
Oil-based drug delivery systems have been studied in different aspects. The present study proposes a new application for an oil-based delivery system, focusing on controlled release until the drug reaches the later part of the small intestine. Bulk surfactants and interfacial surfactants were added into the oil formulation to provide a better mechanistic understating of the lipolysis. Validation of the modified in vitro method shows the overall conversion from medium-chain triglyceride oil (MCT oil) to free fatty acids (FFA) of 100 ± 4% in five replicates. This fully converted level and high reproducibility are fundamental for the following investigations where any retarding effect can be distinguished from the experimental errors. The results show that viscosity and thermodynamic activity have limited retardation. Furthermore, the former may change the kinetics of lipolysis, while the latter changes the equilibrium level. The gel-forming retarder (ethylcellulose) displayed a strong effect. Whereas the lipolysis was significantly retarded (>50%) when the retarders altered the interfacial composition (poloxamer 407), degradable interfacial surfactants did not have the same effect. However, surface-active, lipolysis-resistant retarders with a high CMC did not show a retarding effect.